Analysis of the layout of the Dangerous and Toxic Goods (B3) warehouse using the 5S method (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) on PT Mitra Agung Sejati - Marnova, Bonji; Tung, Tran Minh (Sinergi International Journal of Logistics, 2023)
This research was conducted at PT Mitra Agung Sejati. The purpose of this study is to analyze the layout of dangerous and toxic goods (B3) warehouses using the 5s method (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) at PT Mitra Agung Sejati. The research methodology used in this study is qualitative research method. The results of the study explained that this B3 storage area has not met the 5S principle, namely the absence of sorting, neat and clean arrangement for hazardous and toxic materials and labeling goods. The actual layout of this company is not organized, making operators uncomfortable in picking and storing hazardous and toxic materials to be used or quantities to be stored. However, after being researched and proposed using the 5S method, activities in the warehouse will be more organized and operators will find it easier to pick up goods and store goods such as labeling and making markings for the location of goods and laying work tools and marking for forklift parking. Through the application of this 5S method, the physical condition of the work environment at PT. Mitra Agung Sejati is more neatly organized and affects the comfort of workers.